The life of sociologist Alain Touraine has come to its end. Has it come to The End of Societies as well, as Touraine claimed? - Vratuša, Vera (Sociološki pregled, 2024)
Alain Touraine, the world-famous French sociologist, director and professor at the School for Advanced Studies in the Social Sciences, founder of the Centre for the Analysis and Sociological Intervention in 1981, visiting professor at many universities outside France, and recipient of many national and international awards, died in Paris on June 9, 2023, at 3:30 A.M., at the age of 97. His daughter, Marisol Touraine, former French minister of social affairs, announced to the editorial staff for culture of the French television the exact time and date of her father’s death. This information provoked the appearance of several in memoriam texts, rich in data on Touraine’s biography and bibliography. I will also rely on these data, apart from other secondary and primary sources, in the process of reconstruction of the close relationship between Touraine’s biography and his theoretical, empirical and practical political sociological work.